Continuous-Flow Synthesis of (–)-Oseltamivir Phosphate (Tamiflu) - Sagandira, Cloudius R.; Watts, Paul (Synlett, 2020)
Herein the anti-influenza drug (–)-oseltamivir phosphate is prepared in continuous flow from ethyl shikimate with 54% overall yield over nine steps and total residence time of 3.5 min from the individual steps. Although the procedure involved intermediate isolation, the dangerous azide chemistry and intermediates involved were elegantly handled in situ. It is the first continuous-flow process for (–)-oseltamivir phosphate involving azide chemistry and (–)-shikimic acid as precursor.
Keywords: azide chemistry; continuous flow; influenza; (–)-oseltamivir phosphate; total synthesis